Who is a ‘healthy subject’?: consensus results on pivotal eligibility criteria for clinical trials - Breithaupt-Grögler, Kerstin; Mikus, Gerd (European journal of clinical pharmacology, 2017)
Introduction/Methods A discussion forum was hosted by the German not-for-profit Association for Applied Human Pharmacology (AGAH e.V.) to critically review key eligibility criteria and stopping rules for clinical trials with healthy subjects, enrolling stakeholders from the pharmaceutical industry, contract research organisations, academia, ethics committees and competent authority.Results Pivotal eligibility criteria were defined for trials with new investigational medicinal products (IMPs) or with clinically established IMPs. In general, a pulse rate ranging between 50 and 90 beats/min is recommended for first-in-human (FIH) trials, while wider ranges seem acceptable for trials with clinically established IMPs, provided there are no indications of thyroid dysfunction. Hepatic laboratory parameters not to exceed the upper limit of normal (ULN) comprise ALT (alanine aminotransferase) and AST (aspartate aminotransferase) in FIH trials, whereas slight elevations (10% above ULN) seem acceptable in trials with clinically established IMPs without known hepatotoxicity. A normal renal function is required for any clinical trial in healthy subjects. A risk-adapted approach for stopping rules was adopted. Stopping rules for an individual subject are one adverse event of severe intensity or one serious adverse event. In case of a severe adverse event, some stakeholders demand a causal relationship with the IMP (i.e. an adverse reaction). Stopping rules for a cohort are one serious adverse reaction or ≥50% of subjects experiencing any adverse reaction of moderate or severe intensity.Consequences The application of this consensus resulted in a reduction in protocol deficiencies issued by the competent authority.
Published online: 7 January 2017
Gesehen am 26.06.2018